An Empirical Analysis Of The Impact Of Human Resource Management, Logistic Warehouse, And Production Planning On Company Performance In The Manufacturing Industry - Hamzah Muhammad Mardi Putra; Rahmat Hidayat; Saur Panjaitan (Jurnal Manajemen Industri dan Logistik, 2025)
This study aims to analyze the Factors Affecting Company Performance Through Human Resource Management, Logistics Warehouse, and Production Planning in the Manufacturing Industry in Indonesia. Data were collected through a survey involving 150 employees from several manufacturing industry companies in Indonesia. The results of the study indicate that the Human Resource Management variable has a negative and significant effect on employee performance, Warehouse Logistics, and Production Planning has a positive and significant effect on company performance. The findings reveal that HRM has a negative and significant effect on employee performance, indicating potential issues in HR policies, practices, or implementation that may hinder workforce productivity. These results highlight the importance of reviewing HRM strategies while strengthening logistics and production systems to achieve sustainable performance in the manufacturing sector.